Design, Fabrication And Characterization Of Piezoelectric P(Vdf-Trfe) Thick Film On Flexible Substrate For Energy Harvesting - Lau, Kok Tee; Kok, Swee Leong; Lau, Kok Tee (Penerbit Universiti, UTeM, 2018)
This paper discusses on the design and fabrication steps of piezopolymer using poly(vinylidene fluoride) trifluoroethylene, P(VDF-TrFE) thick film on the flexible substrate using screen-printed method. Polyethylene terephthalate, PET film was used as a substrate to hold P(VDFTrFE) thick film in between sandwiched layers of electrodepiezopolymer-electrode. The P(VDF-TrFE) thick film is then annealed at 100 °C and polarized at 100 V for the film and inspected under EDS, FESEM and XRD for the characterization process. The flexible piezoelectric P(VDFTrFE) thick film is able to generate maximum output peak power of 4.36 µW at an external load of 1kΩ with generated maximum peak-to-peak voltage about 3.0 V for energy harvesting applications when using impact force test from freefall drop plasticine of 0.2 N was applied to the thick film.